If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 14) + -1(9x + 5) = 0 Reorder the terms: (14 + 6x) + -1(9x + 5) = 0 Remove parenthesis around (14 + 6x) 14 + 6x + -1(9x + 5) = 0 Reorder the terms: 14 + 6x + -1(5 + 9x) = 0 14 + 6x + (5 * -1 + 9x * -1) = 0 14 + 6x + (-5 + -9x) = 0 Reorder the terms: 14 + -5 + 6x + -9x = 0 Combine like terms: 14 + -5 = 9 9 + 6x + -9x = 0 Combine like terms: 6x + -9x = -3x 9 + -3x = 0 Solving 9 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -3x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = 0 + -9 -3x = 0 + -9 Combine like terms: 0 + -9 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 3,75100,000= | | y^2-12y+12=0 | | 13=9x+5-5x | | 2a+6+5a=3a-10 | | -12+.2x-.3x+x=6x | | d^5+5d-4=0 | | 6x^2=x+40 | | 2g-16=-8 | | 5x+12=7x-13 | | y^2-12y+62=0 | | 4-3x=2x-6 | | 4-1(m-2)=12 | | x^3-12x=30 | | x^3-5x=3 | | 14-1(-2p+5)=-2p+9 | | 5(x-4)+2x=4x-1 | | 9m=14fraction | | -2(3k-3)=10 | | d^5+5d+4=0 | | -3(3p+5)-2(1-11p)=3(7+4p) | | (x+9)18=12/72 | | -7(3+3b)=-6-6b | | (5p-2)-(2p+7)+(-9p+18)= | | 2y+5=-4-4 | | -2(8x+2)=4(x+6.5) | | 8x-7=42 | | (19b-3)-9(2b+3)=-5 | | x^2+y^2-10x-14y+58=0 | | 3(2+2n)-6(n+2)=-6 | | -3+12=-6-18 | | 4(3x-3)=-8(x+14) | | -(n+3)=72 |